Learning Confidence Intervals with Mobile Devices. - Tapia Moreno, Francisco Javier; Villa Martinez, Hector Antonio (International Journal of Interactive Mobile Technologies (iJIM), 2013)
Mobile learning (m-learning) enhances learning skills in some students. Mobile phones, Tablets, PDAs, Pocket PCs and Internet can be used jointly in order to encourage and motivate learning wherever and whenever students want to learn. In this work, we show learning objects for teaching and learning inferential statistics using mobile devices. With these learning objects, students can calculate confidence intervals based in either a large or a small data sample obtained from a normal or a non-normal population. These objects are been designed for devices with Android operating system.